Who wants a referendum on EU membership? Exploring public attitudes in six Member States. Issue 3 (3rd April 2021) - Eichhorn, Jan; Kenealy, Daniel; Hübner, Christine
ABSTRACT: Using data from a survey conducted in six EU Member States, we explore what drives citizen demand for referendums on EU membership. We examine whether or not similar drivers and mechanisms can be found across the countries surveyed. We consider what are traditionally understood to be the drivers of euroscepticism, exploring whether those same drivers help to explain demand for referendums on EU membership. Our most important finding is that citizens' attitudes to EU referendums are not driven, or explained, by a single issue, or by uniform mechanisms cross-nationally. Although we find that trust in EU institutions is a significant predictor of referendum demand, the impact of other factors considered varies substantially across the six countries.